Non-linear association of cystatin C and all-cause mortality of heart failure: A secondary analysis based on a published database - Zheng, Tao; Tang, A-Mei; Huang, Yuan-Lei; Chen, Jin (Frontiers in Cardiovascular Medicine, 2022)
Background: Prior reports have revealed that basal Cystatin-C (CysC) is positively associated with all-cause death in patients with heart failure (HF). Yet, this positive association is not necessarily generalizable to Chinese HF patients due to methodological limitations and lack of data from Chinese patients. METHODS: We performed secondary data mining based on a retrospective cohort dataset published on the internet. This dataset contains 2008 patients with HF who were admitted to a tertiary hospital in Sichuan Province, China from 2016 to 2019. The exposure variable was baseline CysC and the outcome variable was all-cause death on day 28, day 90, and month 6. Covariates were baseline measurements, including demographic data, drug use, comorbidity score, organ function status (heart, kidney) , and severity of heart failure. RESULTS: Among 1966 selected participants, the mortality rates at 28 days, 90 days and 6 months were 1.83% (36/1966), 2.09% (41/1966) and 2.85% (56/1966) respectively. After adjustment for confounders, the nonlinear associations between CysC and all-cause deaths were observed. We calculated the inflection points were about 2.5 mg/L of CysC. On the right of inflection point, each increase of 1 mg/L in CysC was associated with an increase in the risk of 28-day mortality (Relative risk[RR], 2.07; 95% confidence interval [CI], 1.09 to 3.93; P =0.0266), 90-day mortality (RR, 2.51; 95% CI, 1.38 to 4.57; P=0.003), and 6-month mortality (RR,2.25; 95% CI, 1.37 to 3.70; P<0.001). CONCLUSION: Our findings suggest that values about 2.5 mg/l of cystatin could be a danger threshold for the short-term risk of death in heart failure. . Exceeding this threshold, for every 1 mg/L increase in CysC, the risk of all-cause mortality increased by more than one time.